Transformative Journey with LAFKI: Accreditation of GPM Sumber Hidup Hospitals in Quality Improvement and Patient Safety (Case Study) - Hisnindarsyah, Hisnindarsyah; Wattimena, Mirel; Tuamelly, Jacky; Wahyudi, Ahyar (Formosa Journal of Science and Technology, 2024)
GPM Sumber Hidup Hospital has undergone an accreditation process that reaffirms its commitment to high-quality standards in healthcare services. This process demands compliance with established requirements for the provision of healthcare services. Accreditation from LAFKI (Lembaga Akreditasi Fasilitas Kesehatan Indonesia) is important as it signifies the hospital's alignment with established quality and patient safety standards. The aims of this article is to present findings from a case report study on the accreditation of GPM Sumber Hidup Hospital in the context of improving quality and patient safety. It is hoped that this article can make a significant contribution to the understanding of enhancing the quality and safety of patients within the context of hospital accreditation. By presenting comprehensive and relevant research findings, this article aims to provide valuable insights for healthcare practitioners and researchers in their efforts to improve healthcare service standards.